Gerakan Literasi Sekolah Pada Mata Pelajaran Sejarah Untuk Meningkatkan Hasil Belajar Siswa - Sarwiyoto Sarwiyoto (Jurnal Lingkar Mutu Pendidikan, 2021)
The purpose of writing is to determine the increase in student learning outcomes in Indonesian history subjects after the literacy movement carried out in schools. This study uses the Classroom Action Research Method, starting with pre-cycle activities and then conducting research activities with action cycles 1 and cycle 2. The results of research in class XI IPS 2 obtained pre-cycle value data from 36 people the average value is: 73.06. Minimum Completeness Criteria Value is 75.00. Furthermore, the value in cycle 1 activities is: 78.66. In cycle 2, learning activities have led to the habituation of literacy activities and exploration of teaching materials. So all students of class XI IPS 2 were completed, with an average score of: 84.72. The conclusion of this paper is that the school literacy movement can improve student learning outcomes in Indonesian history subjects